1989
DOI: 10.1111/j.1365-2265.1989.tb01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Foetal Hypothyroidism: Evidence for the Safety of Breast‐feeding While Taking Propylthiouracil

Abstract: We assessed the post-natal thyroid function in eight infants of mothers with Graves' disease whose thyroid function at birth was suppressed by maternal ingestion of propylthiouracil during pregnancy. These mothers continued taking propylthiouracil after delivery and breast-fed exclusively (two mothers supplemented their breast milk with a small amount of baby food). The cord free T4 level was slightly but uniformly below the normal range in all eight infants, and the cord TSH level was above the normal in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…In 1979, Low et al [37], and in 1980, Kampmann et al [38], reported that less than 0.1% of the administered dose of propylthiouracil was detected in the milk of lactating women. Since these observations, there have been a few reports describing the use of propylthiouracil in the treatment of Graves' disease in breast-feeding mothers [38][39][40][41][42].…”
Section: Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…In 1979, Low et al [37], and in 1980, Kampmann et al [38], reported that less than 0.1% of the administered dose of propylthiouracil was detected in the milk of lactating women. Since these observations, there have been a few reports describing the use of propylthiouracil in the treatment of Graves' disease in breast-feeding mothers [38][39][40][41][42].…”
Section: Treatmentmentioning
confidence: 97%
“…The half-life of methimazole in milk is 4.2 ± 0.8 hours, and the mean methimazole concentration decreases to 0.03 ± 0.01 mg/ml after 12 hours. From data available [41,45,51], it can be calculated that following a 20 mg dose of methimazole, the infant may receive approximately 50 mg methimazole. This amounts to 7 mg/kg for a 5-month-old infant weighing 7 kg (or 490 mg methimazole in a 70-kg man).…”
Section: Treatmentmentioning
confidence: 99%
“…The risk is highest when maternal hyperthyroidism is not well controlled, and the diagnosis may not be made until shortly after delivery when the antithyroid drug has been cleared from the neonatal thyroid and circulation. Mothers receiving medication can still nurse their babies as the amount of propylthiouracil and methimazole excreted in breast milk is minimal and neonatal thyroid function is not depressed [1 , 25,26 ]. Furthermore, children nursed by mothers who received methimazole in therapeutic doses exhibited no difference in height, weight, serum concentrations of thyroid hormones and thyroid antibodies, or verbal and functional IQ and their components, when assessed at ages of 48-86 months [26 ].…”
Section: Management Of the Fetus And Neonatementioning
confidence: 98%
“…It is now well established that both PTU and MMI are transferred into the breast milk (23,(34)(35)(36)(37). PTU, which is highly protein-bound, is excreted into the milk in much lower concentrations (0.025%-0.077%) than MMI, which has a serum to milk ratio of 1.…”
Section: Thionamide Therapymentioning
confidence: 99%